Establishment of non‘methyl eugenol‘responding lines from feral Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera Tephritidae) - A. R. A. Mandanayake, Mandanayake; Shohaimi, Shamarina; A. Ghani, Nurul I.; Hee, Alvin K. W. (Springer, 2023)
The Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera Tephritidae), is one of the worlds most destructive and invasive pest of fruits. The control of this insect has relied heavily on the male annihilation technique (MAT).The sterile insect technique (SIT) involves releases of mass-reared sterile male insects to mate with feral females resulting in no progenies produced. In practice, sequential MAT followed by SIT has been used to significantly reduce the population of feral B. dorsalis males before sterile males are released. Thus, combined use MAT and SIT offers excellent control of B. dorsalis. However, issues with sterile males getting killed by going to those MAT traps have reduced the efficacy of both techniques. Nonetheless, the availability of non-MEresponding male B. dorsalis would enable the simultaneous application of MAT and SIT. Therefore, as part of a laboratory-scale proof of concept, the possibility of raising non-methyl eugenol (ME)-responding male B. dorsalis was explored. Non-ME-responding B. dorsalis males obtained from selection of a single generation of wild males through repeated exposures to ME was investigated for their development. Wild B. dorsalis flies reared from infested Syzygium sp. fruits, from four different locations respectively were evaluated for ME attraction. Those males were successively exposed to ME for a total of 9 days in the morning with 24 h interval in between. Non-attraction of males to ME was defined as absence of attraction in at least two successive exposures. We report from those assays, progress in establishment of two separate lines of non-ME-responsive males.